Heterotopic Moments of Being in Clarice Lispector’s The Besieged City - Kasima, Tetyana (Semiotika, 2024)
The paper examines the novel A Cidade Sitiada, 1949 (The Besieged City, 2019) by Clarice Lispector, a work often overlooked yet rich in the exploration of urban transformation and subjective experience of city life. Through the character of Lucrécia Neves, Lispector presents a multifaceted view of São Geraldo, a fictional city undergoing significant change, and captures the psychological impact of these shifts on its inhabitants. The analysis focuses on what I term heterotopic moments of being, instances where the protagonist’s perception of her environment reveals the city’s layered and shifting nature. These moments draw on the Foucauldian concept of heterotopia, combining it with the notion of “moments of being” introduced by Virginia Woolf. By examining the moments, I aim to highlight how Lispector negotiates the boundaries between permanence and transience and fluidity and solidity in urban spaces. Methodologically, the study involves close reading and the concepts of literary urban studies in the examination of the passages from The Besieged City that vividly depict the transformations of the city. My study seeks to reveal how Lispector’s work contributes to the literary portrayal of urban space as an orienting and disruptive force, shaping characters’ perceptions of self, place, and the fluid boundaries between them.
Keywords: moments of being; heterotopia; Clarice Lispector; city; The Besieged City